The Honourable Robert Edward Clifford (1767-1817): Maps and Mysteries - Moulder, Cathy (My University, 2008)
Robert Clifford was an Englishman, a renowned map collector – and probably a spy. He lived a quiet scholarly life in Paris during the French Revolution and early years of the Napoleonic era. But his correspondence with John Graves Simcoe reveals an exciting escape from France in 1803 with a trunk of secret maps and plans. Could the maps in McMaster University Library's collection have been part of that daring escape?
Keywords: Robert Clifford; map collector; maps; mysteries; Library and Information Science; Library and Information Science